Survey on reporting of epithelial cells in urine sediment as part of external quality assessment programs in Brazilian laboratories - Poloni, José A. T. (Array, 2021)
Epithelial cells (ECs) are structures regularly observed during urine microscopy analysis. The correct identification of EC subtypes can be useful since renal tubular epithelial cells (RTECs) are clinically relevant. We investigate the urinary ECs report and the judgement of its clinical importance by Brazilian laboratories.A survey with four questions was made available to participants of the Urinalysis External Quality Assessment Program (EQAP) from Controllab. Laboratories composed 3 groups: (1) differentiating ECs subtypes: "squamous", "transitional" and "RTECs"; (2) differentiating ECs subtypes: "squamous" or "non-squamous" cells; (3) without ECs subtype identification. Participants did not necessarily answer to all questions and the answers were evaluated both within the same laboratory"s category and within different categories of laboratories.A total of 1336 (94%) laboratories answered the survey; Group 1, 119/140 (85%) reported that ECs differentiation is important to the physician and 62% want to be evaluated by EQAP, while in Group 3, 455/1110 (41%) reported it is useful to them, however only 25% want be evaluated by EQAP. Group 2 laboratories 37/51 (73%) reported that the information is important, but only 13/52 (25%) are interested in an EQAP with differentiation of the 3 ECs subtypes.Most of the laboratories do not differentiate ECs in the three subtypes, despite the clinical importance of RTECs. Education of laboratory staff about the clinical significance of urinary particles should be considered a key priority.